Kemampuan Menulis Teks Biografi Berbantuan Media Audiovisual Siswa Fase E SMK Negeri 1 Painan Kabupaten Pesisir Selatan - Eva Fitrianti; Susanti Marisya; Fuji Rahayu (Kilau Publishing, 2025)
This study is grounded in the condition that teachers rarely use audiovisual media in the learning process, which causes students to frequently experience difficulties in mastering biographical texts. The study aims to describe the biographical text writing skills of Phase E students at SMK Negeri 1 Painan, Pesisir Selatan Regency, through the use of audiovisual media. This research employed a quantitative approach with a descriptive method. The population consisted of 106 students, while the sample was determined using purposive sampling. The findings show that the overall ability to write biographical texts with audiovisual media support was classified as good (G), with a mean score of 76.40, falling within the 76–85% range on the 10-point scale. More specifically, the indicators reveal that pronoun use was classified as good (G) with a mean score of 84.37 (76–85%), action verbs were classified as excellent (E) with a mean score of 97.91 (96–100%), and adjectives were classified as more than adequate (MTA) with a mean score of 70.15 (66–75%). Furthermore, passive verbs were classified as adequate (A) with a mean score of 61.92 (56–65%), while the use of time-sequence conjunctions was classified as poor (P) with a mean score of 38.69 (36–45%) on the 10-point scale.